2017
DOI: 10.1016/j.eats.2016.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Flexor Hallucis Longus Tenosynovitis and First Metatarsophalangeal Synovitis After Penetrating Nail Prick Injury: Treated by Zone 3 Flexor Hallucis Longus Tendoscopy and Metatarsosesamoid Arthroscopy

Abstract: Pedal penetrating nail prick injury around the first metatarsal head can result in persistent synovitis of the first metatarsophalangeal joint and tenosynovitis of the flexor hallucis longus tendon. Exploration and debridement is indicated if the condition does not improve with antibiotics. Open surgery requires extensive dorsal and plantar incisions. The purpose of this Technical Note is to report the combined arthroscopic and tendoscopic approaches to address the first metatarsophalangeal joint and flexor ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Most of the previously reported cases are just local lesions, and most of the patients have a history of big toe trauma or special occupations such as ballerinas or professional athletes, who have tendon sheath stenosis and wedge pressure-caused tendon sliding disorder, so it can be easily diagnosed. 4,9,10 Another type of easily identifiable case is the case combined with os trigonum and posterior malleolus impact, in which FHLT-E may be found coexisting during treating the posterior malleolus impact. 11,12…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the previously reported cases are just local lesions, and most of the patients have a history of big toe trauma or special occupations such as ballerinas or professional athletes, who have tendon sheath stenosis and wedge pressure-caused tendon sliding disorder, so it can be easily diagnosed. 4,9,10 Another type of easily identifiable case is the case combined with os trigonum and posterior malleolus impact, in which FHLT-E may be found coexisting during treating the posterior malleolus impact. 11,12…”
Section: Discussionmentioning
confidence: 99%
“…3 Its clinical manifestations are diverse, and some cases manifest inaccurate ankle discomfort and pain. Michelson and Dunn 1 reported 81 patients with diffuse pain in the middle and posterior foot, most of whom were misdiagnosed as "plantar fasciitis" and then underwent erroneous treatment; some cases manifest local symptoms; Lui 4 once reported a group of patients with nail prick injury-caused FHLT and the first metatarsophalangeal synovitis, which manifested swelling and pain at the distal end of the first metatarsophalangeal joint; some cases have no clinical symptoms. Lohman et al 5 used magnetic resonance imaging (MRI) and observed asymptomatic sheath effusion of FHL after long-distance running in healthy people.…”
Section: Introductionmentioning
confidence: 99%
“…Extra-articular causes should be managed by other appropriate procedures such as metatarsal osteotomy 11 or flexor hallucis longus tendoscopy. 12 , 13 , 14 To provide effective treatment of the intra-articular causes, complete arthroscopic adhesiolysis with synovectomy and debridement of the damaged cartilage of the metatarsosesamoid compartment should be performed. If there is fragmentation of the sesamoid bone signifying severe sesamoiditis, arthroscopic sesamoidectomy should also be performed.…”
Section: Discussionmentioning
confidence: 99%
“…If there is fragmentation of the sesamoid bone signifying severe sesamoiditis, arthroscopic sesamoidectomy should also be performed. 9 , 10 , 14 …”
Section: Discussionmentioning
confidence: 99%
“…Lui T H described in the context of minimally invasive approach, the combined arthroscopic and tendoscopic procedure to manage FHL septic tenosynovitis and first metatarsophalangeal (MTP-1) synovitis after prick injury [36]. According to the author, the advantages of this technique include small incisions which provides better cosmetic results, less chance of painful scar formation and thorough exploration and debridement of the FHL tendon and the MTP-1 joint [36].…”
Section: Discussionmentioning
confidence: 99%